2021
DOI: 10.17762/itii.v9i2.464
|View full text |Cite
|
Sign up to set email alerts
|

Embryotoxicity and Teratogenic Effects of Parmotrema Tinctorum (Nyl) Hale on Zebrafish (Danio Rerio) and Cytotoxic Activity of Lichen Extract on Hek293t Cell Line

Abstract: Parmotrema tinctorum (Nyl) Hale an edible lichen, used as a spice and flavouring agent for meat and vegetable preparations by ethnic groups in India and Nepal. In Zebrafish embryos and larva, the therapeutic applications of P.tinctorum widely reported. However the teratogenic effects not  reported. This study was aimed to examine the toxicity of P.tinctorum on the promising model for toxicity research, the Zebrafish, because their genetic structure is more similar to human beings. Additionally, we have demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The embryos exhibited good health and did not have any morphological defects. The results indicated that the safety was maintained at concentrations of up to 200 µg/mL [21].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The embryos exhibited good health and did not have any morphological defects. The results indicated that the safety was maintained at concentrations of up to 200 µg/mL [21].…”
Section: Discussionmentioning
confidence: 93%
“…The Indian Siddha system was a renowned traditional form of treatment that had been employed since ancient times to heal a wide range of illnesses. Ayurvedic Indian medicine was used in several lichen extracts as remedies for various ailments [21]. The phytochemical test of P. perlata extract was evaluated for qualitative analysis.…”
Section: Discussionmentioning
confidence: 99%